2011
DOI: 10.4322/floram.2011.023
|View full text |Cite
|
Sign up to set email alerts
|

O Uso de Dispositivos de Segurança Alternativos Para Reduzir Acidentes de Trabalho na Operação com Serras nas Indústrias Madeireiras

Abstract: Os cuidados necessários para o manuseio de serra circular e serra destopadeira são indispensáveis para a redução de acidentes e maior ganho em produtividade. Pensando nesta questão, o trabalho desenvolvido propôs pesquisar, testar e comparar formas rápidas e baratas que permitam adaptar dispositivos que evitem acidentes sem reduzir a produtividade, requisito básico para o aumento do bem-estar do indivíduo e aumento da competitividade da empresa. Entretanto, a atividade de operação de equipamentos industriais, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Guimarães et al (2018) measured the variables thermal comfort, wind speed, illuminance and noise for a factory of production of forest tools with wood handles, and concluded that the activity occurred in thermal discomfort in the afternoon shift, with wind speeds below 0.75 m/s, poor illuminance and noise, medium, above what is tolerated for an eight-hour workday and without hearing protection. A simple and inexpensive way to prevent accidents at work without reducing productivity is to issue personal protective equipament (PPE) to employees, while also reinforcing safety during operation (HEGEDUS et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Guimarães et al (2018) measured the variables thermal comfort, wind speed, illuminance and noise for a factory of production of forest tools with wood handles, and concluded that the activity occurred in thermal discomfort in the afternoon shift, with wind speeds below 0.75 m/s, poor illuminance and noise, medium, above what is tolerated for an eight-hour workday and without hearing protection. A simple and inexpensive way to prevent accidents at work without reducing productivity is to issue personal protective equipament (PPE) to employees, while also reinforcing safety during operation (HEGEDUS et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, Hegedus et al (2011) states that accidents that lead to amputation of limbs such as fingers, arms and hands occur mainly due to the use of cutting machines and that in 2001, the segments of sawmills and joinery were responsible for 15% of all cases of amputations in work environments.…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%
“…No contexto deste estudo, destacaram-se as serras como o principal agente causador das lesões; as fraturas prevaleceram como o tipo de lesão mais comum; e o membro mais acometido foram os dedos. Hegedus et al (2011), em seu estudo constatou que as lesões permanentes decorrentes de acidente ocorriam com dois tipos de máquinas de serras: circular e destopadeira, utilizadas no processo de desdobro e processamento de madeira, para isso levantou as empresas que processavam madeira na região e quantificou os números de acidentes de trabalho com suas consequências e impactos, buscando a compreensão do processo do cenário do acidente, na tentativa de propor soluções simples de prevenção e proteção nas operações, sem que com isso ocorresse a diminuição ou perda da produção, e ainda melhorar a segurança do trabalho, nessas empresas de madeira. Souza et al (2008) apontaram que o lado esquerdo foi acometido em 55% dos casos de lesão de mão.…”
Section: Características Das Lesões De Trabalho Envolvendo Membros Suunclassified